2014
DOI: 10.1096/fasebj.28.1_supplement.261.2
|View full text |Cite
|
Sign up to set email alerts
|

Phloridzin fatty acid esters induce apoptosis and alters gene expression in human liver cancer cells (261.2)

Abstract: Phloridzin Fatty Acid Esters Induce Apoptosis and Alters Gene Expression in Human Liver Cancer Cells Sandhya VG Nair, Ziaullah, HP Vasantha Rupasinghe*Department of Environmental Sciences, Faculty of Agriculture, Dalhousie University, Truro, NS B2N 5E3, Canada Abstract Phloridzin (phloretin 2‐O‐glucoside) is a dihydrochalcone, which is specifically found in apple and well known for its beneficial biological effects. To date, there is no report of antiproliferative effect of phloridzin on human cancer cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The production of lipophilic flavonoids and their improved activity against these two cell lines (compared to that of their parent compounds) have previously been exemplified in the literature. For example, Omonga et al demonstrated that O-alkyl derivatives of chrysin increased activity against HCT116; whilst Nair et al demonstrated fatty esters of phloridzin increased the inhibitory effects against MDA-MB-231 [61,62]. Further, our group also found that lauroyl, octanoyl and palmitoyl derivatives of quercetin and luteolin had the greatest improvements against these two cell lines.…”
Section: Antiproliferative Activity Studies Of the Productsmentioning
confidence: 69%
“…The production of lipophilic flavonoids and their improved activity against these two cell lines (compared to that of their parent compounds) have previously been exemplified in the literature. For example, Omonga et al demonstrated that O-alkyl derivatives of chrysin increased activity against HCT116; whilst Nair et al demonstrated fatty esters of phloridzin increased the inhibitory effects against MDA-MB-231 [61,62]. Further, our group also found that lauroyl, octanoyl and palmitoyl derivatives of quercetin and luteolin had the greatest improvements against these two cell lines.…”
Section: Antiproliferative Activity Studies Of the Productsmentioning
confidence: 69%
“…PZ-DHA is a fatty acid ester of PZ (Figure 1) [20] formed through an acylation reaction. Of the six fatty acid esters tested, PZ-DHA was the most effective chemotherapeutic agent [21]. ceptors that TNBCs lack.…”
Section: Introductionmentioning
confidence: 98%
“…PZ-DHA is a fatty acid ester of PZ (Figure 1) [20] formed through an acylation reaction. Of the six fatty acid esters tested, PZ-DHA was the most effective chemotherapeutic agent [21]. Treatment with PZ-DHA significantly downregulates the expression of cancerpromoting genes in HepG2 cells, while having little cytotoxic effect on normal human and rat hepatocytes [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations